Interferensi Fonologi Wasedaboys terhadap Nama-Nama Daerah Indonesia pada Vlog Nihongo Mantappu - Rahardjo, Hardianto (Vocational College of Diponegoro University, 2024)
Interference is a mistake that is generally made by second language learners because of the influence of their first language skills. Meanwhile, phonological interference is an error that occurs at the sound level due to changes in phonemes that are influenced by knowledge of the sound system in the first language. This proposal discusses the mistakes of second language learners (in this case, Wasedaboys) in understanding sound changes that occur in the language being studied (Indonesian). This study aims to describe the forms and factors that cause phonological interference by Wasedaboys in writing the names of regions in Indonesia in the vlog